PENGARUH ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP FIRM VALUE (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Muhammad Alfendy Tri Harjanto; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) and Good Corporate Governance (GCG) on Firm Value. The independent variables in this study include ESG, board of commissioners size, board of commissioners political affiliation, board of commissioners gender diversity, and audit committee size. Then, the dependent variable in this study is firm value and the control variable in this study is leverage ratio.The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2021-2023 and sample collection using the nonprobability sampling method with purposive sampling technique. The analysis used in this study uses multiple linear analysis with the help of IBM SPSS 25 software.The results of the study indicate that ESG is positive and significant on firm value. On the other hand, gender diversity of the board of commissioners has a positive and insignificant effect on firm value and political affiliation of the board of commissioners and the size of the audit committee have a negative and insignificant effect on firm value.